1999
DOI: 10.1002/(sici)1521-4184(19996)332:6<195::aid-ardp195>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

[meso-1,2-Bis(2,6-dichloro-4-hydroxyphenyl)ethylenediamine]sulfato-platinum(II) — Pharmacokinetic Studies

Abstract: The maximally attainable level of the non‐plasma protein bound fraction of a single 10.0 μmol/kg i.p. dose of [meso‐1,2‐bis(2,6‐di‐chloro‐4‐hydroxyphenyl)ethylenediamine]sulfatoplatinum(II), a drug active on the murine, hormone‐sensitive MXT‐M‐3.2 breast cancer, lies markedly below the concentration causing a significant cytotoxic effect on a cell line derived from this tumor. This result confirms our opinion that the strong in vivo activity of this drug on hormone‐sensitive breast cancers is mediated by its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Antitumor activity of meso-1-PtCl2, DES, E2, cDDP and ovariectomy on the hormone-sensitive MXT-M-3.2 mammary carcinoma in NMRI (nu/nu) mice, age 10 weeks. of action, which is based on their hormonal potency [1,2] . Indications that estrogens can modify the immune response in patients [5,[11][12][13][14][16][17][18][19] induced us to examine, if meso-1-PtCl 2 brings about its anti-breast cancer activity in rodents by enhancement of the body defense.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antitumor activity of meso-1-PtCl2, DES, E2, cDDP and ovariectomy on the hormone-sensitive MXT-M-3.2 mammary carcinoma in NMRI (nu/nu) mice, age 10 weeks. of action, which is based on their hormonal potency [1,2] . Indications that estrogens can modify the immune response in patients [5,[11][12][13][14][16][17][18][19] induced us to examine, if meso-1-PtCl 2 brings about its anti-breast cancer activity in rodents by enhancement of the body defense.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the MXT-M-3,2 breast cancer implanted into female B6D2F 1 mice accelerates the growth of an identical second tumor and that this process is reversed to an inhibition by meso-1-PtCl 2 by virtue of its estrogenic potency [1,2,20] . We have supposed that the anti-breast cancer effect of meso-1-PtCl 2 and also of other estrogenic compounds (compare ref.…”
Section: Full Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of the animal experiments is thoroughly described in the preceding publications [1][2][3] .…”
Section: Experimental Partmentioning
confidence: 99%